Sex Differences in Circulating T-Tau Trajectories After Sports-Concussion and Correlation With Outcome - Mondello, Stefania; Guedes, Vivian A.; Lai, Chen; Jeromin, Andreas; Bazarian, Jeffrey J.; Gill, Jessica M. (Frontiers in Neurology, 2020)
Sex differences in molecular biomarkers after sports-related concussion (SRC) could steadily advance our understanding of injury heterogeneity and complexity, and help capture phenotypic characteristics, by unveiling sex-dependent pathobiological processes and disease mechanisms. Such knowledge will help improve diagnosis, clinical management, and prognosis. Total-tau (t-tau) has recently emerged as a promising blood marker showing sex-associated differences in neurodegenerative diseases. Nonetheless, to date, little is known about the potential influence of sex on its injury-related concentration and dynamics after SRC. We hypothesized that measurements of circulating levels of t-tau over time would reflect a differential vulnerability signature, providing insights into the sex-related phenotypes and their relationship with clinical outcomes. To test this hypothesis, plasma levels of t-tau were measured using an ultrasensitive immunoassay up to 7 days after injury, in 46 concussed athletes (20 males, 26 females). We used trajectory analysis to generate two distinct temporal profiles of t-tau, which were then compared with gender and return to play (RTP). The majority of subjects (~63%) started with low t-tau concentrations that further declined within the first 48 hours; while the remaining (‘maximal decliners’) started with concentrations similar to the baseline levels that also fell over time but persisting markedly higher compared with the first profile. The maximal decliner group was primarily composed of female subjects (p=0.007) and was significantly associated with poor outcome (RTP ≥10 days after concussion) (p=0.011). Taken together, our data provide evidence for the existence of sex-related biosignatures following sports-related concussions, possibly indicating a differential effect as a result of distinct brain vulnerability and inherent injury response. Future studies will be required to further elucidate underlying sex-based biological and pathophysiological mechanisms, and determine the value of t-tau signatures for management and therapeutic decision-making in sports-related concussions.